Efektifitas Pembelajaran Pendidikan Jasmani secara Daring Selama Pandemi Covid-19 - Giri Verianti; Mohamad Najib (Nusa Putra University, 2022)
Physical education as a formal class is under threat in many schools as the implementation of basic education diminishes, and the demand for bold education results in the need for courses that meet standards for all fields of study, including physical education. The purpose of this research is to see how physical education subjects boldly affect students' learning and their ability to meet fitness and health requirements with national standards. in accordance with the implementation of physical education boldly is related to reduced subjects, such as the ability to hold students accountable. According to research, the right mix of meaningful learning activities, specific learning goals, and attracting student accountability increases student motivation and activates physical activity in bold learning. The activity diary components, parental accountability and monitoring, and freedom of choice in activities are all included in suggestions for implementing bolder physical education learning that is more successful